Association between depression and stroke risk in adults: a systematic review and meta-analysis - Ashraf, Farheen; Mustafa, Muhammad Saqlain; Shafique, Muhammad Ashir; Haseeb, Abdul; Mussarat, Abdullah; Noorani, Amber; Sohail Rangwala, Burhanuddin; Kashif Rasool, Fatimah; Siddiq, Mohammad Arham; Iqbal, Javed (Frontiers in Neurology, 2024)
Introduction Stroke is a significant global health concern, and numerous studies have established a link between depression and an increased risk of stroke. While many investigations explore this link, some overlook its long-term effects. Depression may elevate stroke risk through physiological pathways involving nervous system changes and inflammation. This systematic review and meta-analysis aimed to assess the association between depression and stroke. Methodology We conducted a comprehensive search of electronic databases (PubMed, Embase, Scopus, and PsycINFO) from inception to 9 April 2023, following the Preferred Reporting Items for Systemic Review and Meta-analysis (PRISMA) and Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. We included all articles assessing the association between different stroke types and depression, excluding post-stroke depression. Two investigators independently extracted data and assessed quality using the Newcastle–Ottawa Scale and Cochrane Risk of Bias tool, utilizing a random-effects model for data synthesis. The primary outcome was the association of depression with stroke, with a secondary focus on the association of antidepressants with stroke. Results The initial search yielded 10,091 articles, and 44 studies were included in the meta-analysis. The pooled analysis revealed a significant association between depression and stroke risk, with an overall hazard ratio of 1.41 (95% CI 1.32, 1.50; p < 0.00001), indicating a moderately positive effect size. Subgroup analyses showed consistent associations with ischemic stroke (HR = 1.30, 95% CI 1.13, 1.50; p = 0.007), fatal stroke (HR = 1.39, 95% CI 1.24, 1.55; p < 0.000001), and hemorrhagic stroke (HR = 1.33, 95% CI 1.01, 1.76; p = 0.04). The use of antidepressants was associated with an elevated risk of stroke (HR = 1.28, 95% CI 1.05, 1.55; p = 0.01). Conclusion and relevance This meta-analysis indicates that depression moderately raises the risk of stroke. Given the severe consequences of stroke in individuals with depression, early detection and intervention should be prioritized to prevent it. Systematic review registration Prospero (CRD42023472136).